PENGARUH PROFITABILITAS, FINANCIAL LEVERAGE, UKURAN PERUSAHAAN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR - Kefa Merindra Kinanthi Novena; Rilo Pambudi (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2025)
This study aims to analyze the effect of profitability on earnings management, the effect of financial leverage on earnings management, the effect of firm size on earnings management, and the effect of institutional ownership on earnings management. The research objects are manufacturing companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study employs a purposive sampling method and obtains 219 sample observations. The data used are secondary data obtained from the IDX website and the respective companies websites. The data analysis methods used are descriptive statistics and multiple linear regression using SPSS 19 software. The results indicate that profitability has an effect on earnings management, financial leverage has an effect on earnings management, firm size has no effect on earnings management, and institutional ownership has no effect on earnings management.